2020
DOI: 10.3389/feduc.2020.570988
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teachers’ Attitudes and Teacher Efficacy for Inclusive Education on Emotional Distress in Primary School Teachers in Japan

Abstract: The purpose of this study is to examine the relationship between teachers' attitudes toward and teacher efficacy in inclusive education, and the emotional distress in Japan. A survey of 158 primary school teachers in Yamaguchi prefecture, Japan measured the attitudes of regular and special education teachers for inclusive education and teacher efficacy toward inclusive education to assess the impact of these factors on teachers' emotional distress. The results indicated that the teachers' emotional distress wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These findings are consistent with previous studies which reported that the attitude and behavior of the teachers affect the students" performance in the class. 11,12 Attitude of teachers has a significant role in the learning of nursing students as 100% of participants of the current study agreed that the attitude of nursing teachers can affect students" learning. Literature also supports these findings; A good teacher has a positive effect on students" learning and development through the knowledge of all the contents, the expertise of different teaching methods, and communication skill.…”
Section: Discussionmentioning
confidence: 77%
“…These findings are consistent with previous studies which reported that the attitude and behavior of the teachers affect the students" performance in the class. 11,12 Attitude of teachers has a significant role in the learning of nursing students as 100% of participants of the current study agreed that the attitude of nursing teachers can affect students" learning. Literature also supports these findings; A good teacher has a positive effect on students" learning and development through the knowledge of all the contents, the expertise of different teaching methods, and communication skill.…”
Section: Discussionmentioning
confidence: 77%
“…Over decades research has shown that determining attitudes, perceptions and beliefs of student teachers is a complex endeavor as there are intricate personal (e.g., experiences, knowledge, training and level of self-efficacy) and contextual (local, national and global) influences (such as political-ideological-and historical backgrounds, socio-economic circumstances and education system structures) that could have an impact on these views. For example, limited educational resources (i.e., human, support, as well as teaching and learning equipment and material) and inadequate training could have an influence on how the practicality of inclusive education is perceived (Nagase et al, 2020;Kunz et al, 2021;Parey, 2021). How an education system is structured (i.e., full inclusion, or mainstream and special education) also seem to have an impact on how positively or negatively the viability of inclusive education is viewed (Nel, 2018;Friesen and Cunning, 2020).…”
Section: Background To This Study International Contextmentioning
confidence: 99%
“…Teachers who have this attitude project a good level of emotional intelligence which contribute to efficiency, efficacy, and satisfaction towards work. Moreover, Nagase et al (2020) also pointed out that teachers who project an overall positive attitude make a positive impact as well on their students in terms of greater academic gains (in reference to their peers). Thus, it is important for a teacher to possess a high level of emotional intelligence, to remain positive and strong-willed, and to be motivated as these greatly affect their students in many ways which can shape their learning experience.…”
Section: Theme 3: Attitude and Aspirationsmentioning
confidence: 99%